EXPERIMENTAL INVESTIGATION OF NEWLY DEVELOPED ELECTROLYTIC MAGNETIC ABRASIVE FINISHING SETUP WITH MULTIPLE POLE SYSTEM FOR FINISHING OF ALUMIUM WORKPIECE - Malpotra, Anil; Singh, Beant; Singh, Lakhvir (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The procedure of combining abrasion machining with chemical machining is the most demanding and crucial method of machining, because it guarantees higher levels of quality from the part. Combined procedure for machining are typically employed as the last step in the machining process, and their significance grows progressively crucial while a nano finished surface of the work piece material is necessary. The subject of nano surface finishing of materials via chemical machining and abrasion has advanced recently. Electrolytic magnetic abrasive finishing (EMAF) is a procedure that combines chemical and magnetic energy to achieve a desire finish. During the EMAF process, The work piece fits in the middle among two magnetic poles. A mixture of abrasives and ferromagnetic particles fills the gap between each pole and the workpiece. The electrode is positioned at a certain distance from the workpiece, and both are linked to a direct current (DC) power source. An electrolytic solution is circulated between the gap using a pump. The method offer a wide range of industrial applications because to its low specific energy consumption and enhanced surface finishing. This study presents the creation of a novel EMAF with multiple pole system. It further looks into the impact of different process attributes include machining time, rotational speed, size of the abrasive particles, electrolytic concentration and weight of the abrasive particles on the improved performance of material removal rate (MRR) and surface finishing (PISF).